2021
DOI: 10.2337/figshare.16701832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Empagliflozin Treatment is Associated With Improvements in Cardiac Energetics and Function and Reductions in Myocardial Cellular Volume in Patients With Type 2 Diabetes

Abstract: Sodium–glucose-cotransporter-2 (SGLT2) inhibitors reduce the risk of major adverse CV events and hospitalization for heart failure in type 2 diabetes (T2D) patients. Utilising cardiovascular magnetic resonance imaging (CMR) and 31phosphorus magnetic resonance spectroscopy(<sup>31</sup>P-MRS) in a longitudinal cohort study, we aimed to investigate the effects of the selective SGLT2i empagliflozin on myocardial energetics, cellular volume, function and perfusion. Eighteen T2D patients underwent CMR a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Phosphorus-cardiovascular magnetic resonance spectroscopy ( 31 P-CMRS) 31 P-CMRS was performed to obtain the PCr/ATP from a voxel placed in the mid-ventricular septum, with subjects lying supine and a 31 P transmitter/receiver cardiac coil (Rapid Biomedical GmbH, Rimpar, Germany) placed over the heart, in the iso-center of the magnet on a 3T CMR system (Prisma, Siemens Healthineers, Erlangen, Germany) as previously described [9].…”
mentioning
confidence: 99%
“…Phosphorus-cardiovascular magnetic resonance spectroscopy ( 31 P-CMRS) 31 P-CMRS was performed to obtain the PCr/ATP from a voxel placed in the mid-ventricular septum, with subjects lying supine and a 31 P transmitter/receiver cardiac coil (Rapid Biomedical GmbH, Rimpar, Germany) placed over the heart, in the iso-center of the magnet on a 3T CMR system (Prisma, Siemens Healthineers, Erlangen, Germany) as previously described [9].…”
mentioning
confidence: 99%
“…The first study examining SGLT2i and cardiac PCr/ATP, demonstrated that acute treatment with empagliflozin, dapagliflozin or canagliflozin was without effect on PCr/ATP in healthy isolated mouse hearts [69]. In T2DM patients that were treated for 12 weeks with empagliflozin, myocardial PCr/ATP ratio increased significantly from 1.52 to 1.76, together with increases in cardiac function [169]. However, in another study no effect of a 12 weeks empagliflozin treatment on cardiac PCr/ ATP ratio was observed in overweight T2DM patients [170].…”
Section: Energeticsmentioning
confidence: 99%
“…The CMR protocol (Supplementary Material, scan protocol figure) consisted of cine imaging with a steady-state free precession sequence, native pre-and postcontrast T1 mapping, stress and rest perfusion, and LGE. diabetesjournals.org/care Native T1 maps were acquired in three short-axis slices, including segments with maximal wall thickness, with use of a breath-held modified look-locker inversion recovery acquisition as previously described (23). Postcontrast T1 mapping acquisition was performed 15 min after last contrast injection.…”
Section: Cmrmentioning
confidence: 99%
“…While the precontrast native T1 map measurements were comparable across the groups, median myocardial ECV measurements were significantly higher for the HCM groups (HV 25% [interquartile range 23-26], HCM 27% [22][23][24][25][26][27][28][29][30][31], HCM-DM 31% [27-43]; P = 0.006) (Supplementary Material).…”
Section: Myocardial Fibrosis and Scar Burdenmentioning
confidence: 99%
See 1 more Smart Citation